EKSTRAK FENOLIK KULIT BATANG POHON BAWANG HUTAN (Scorodocarpus borneensis Becc.) SEBAGAI ANTIOKSIDAN UNTUK MENGHAMBAT KERUSAKAN FILLET IKAN OLEH BAKTERI PROTEOLITIK - Mastira, Susi; Kusuma Dewi, Yohana Sutiknyawati; Lestari, Oke Anandika (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTPhenolic extract of stem bark of the garlic tree (Scorodocarpus borneensis Becc.) as an antioxidant to inhibit distruction of fish fillets by proteolytic bacteria has been studied. The aim of the study was to determine relationship of the concentration of phenolic extract (methanol:aquades 70/30 v/v) stem bark of the garlic tree with ist antioxidant and inhibitory the destruction of fish fillets by proteolytic bacteria. The study was carried out by maceration of the wood garlic stem bark using methanol:aquades (70:30 v/v). While percent growth inhibition of proteolytic bacteria was expressed descriptively. The results showed total phenol of 100 ppm extract (70 MeOH: 30 H2O, v/v) stem bark of the garlic tree was 463.87 Â± 2.73 mg GAE / g. Antioxidant activity of 100 ppm was 93.07%. Immersion in 10% solution of phenolic antioxidant extract stem bark of the garlic tree able to inhibit the growth of proteolytic bacteria which resulted in microbial damage of fish fillets during storage at 15Â° . Â Keywords : antioxidant, proteolytic bacterial, phenolic, stem bark of the garlic tree